HUBUNGAN POLA PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) DENGAN STATUS GIZI PADA BALITA USIA 6-12 BULAN DI DESA KALIORI KECAMATAN KALIBAGOR KABUPATEN BANYUMAS - Dewi, Ratna Kartika; Pantiawati, Ika; Happinasari, Ossie (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2010)
Malnutrition condition on infant and under five years children is caused by the habit of improper feeding pattern of food supplementing mother’s milk. The presence of this health disadvantaging habit, directly and indirectly will be a main cause of malnutrition problem occurrence. This research aimed to find out relationship between feeding pattern of food supplementing mother’s milk and nutritional status of under five years children 6-12 months age in Kaliori Village Kalibagor Subdistrict Banyumas Regency in 2010. This research used a time approach descriptive correlative method. It was a cross sectional research. The research population was 49 under five years children 6-12 months age in Kaliori Village Kalibagor Subdistrict Banyumas Regency in 2010. It used a purposive sampling and data were analyzed by using Kendall’s tau. 1) Under five years children 6-12 months age in Kaliori Village majority (25 children, 51%) had sufficiently good feeding pattern of food supplementing mother’s milk; 2) Under five years children 6-12 months age in Kaliori Village majority (43 children, 88%) had good nutritional status; 3) Calculation result of relationship between feeding pattern of food supplementing mother’s milk and nutritional status of under five years children 6-12 months age was obtained value of z calculation 0,596 > z table 0,281, thus Ha was accepted, meaning there was a sufficiently strong relationship. There is a sufficiently strong relationship between feeding pattern of food supplementing mother’s milk and nutritional status of under five years children 6-12 months age. For mothers, it should improve the knowledge about feeding pattern of food supplementing mother’s milk because it is highly benefit both for mothers themselves and under five years children. Key words: Food supplementing mother’s milk, Nutritional status